Margadh na Míol I Valparaíso - Rosenstock, Gabriel,Ó Searcaigh, Cathal,Bushe, Paddy (Cló lar-Chonnacht, 2013)
Collected poems of Gabriel Rosenstock from various collections.
Description based on publisher supplied metadata and other sources